An action research for enhancing student understanding of science literacy in stoichiometry by using flash-based learning media - Raditya Wisnu Saputra; Mitarlis Mitarlis (Jurnal Pijar Mipa, 2022)
The research aims to determine the influence of flash media on students' understanding of scientific literacy in stoichiometry. The research method used one group pretest-posttest design. The research was conducted in the tenth grade in one of the State Senior High schools in Gresik, East Java, Indonesia. The three meetings in action research were running well. However, there are obstacles where the device used is very limited, so teachers need to find the solution. Student activity during learning gets a percentage average of 87.67%. It means students were very active. Student learning outcomes show that 97% of students complete the standard minimum of completeness, 34 students complete, and one student does not complete. The Wilcoxon test shows a significantly average student learning outcomes, and the n-gain value for all students of 0.72 is relatively high. The results of the percentage of students' positive responses of 87% are classified as very good. In conclusion, learning by using flash media can be accepted by students and increase their understanding of scientific literacy on stoichiometry.